Report of the Working Group of the Planning Commission on Libraries and Informatics for the Ninth Five Year Plan 1997-2002 - Planning Commission (Planning Commission, 1996)
The changing global and national scenario is bound to make greater demands on communication. Our policy framework and approach to Library and Informatics planning has to be geared to face this demand. The need and importance of information has been felt due to its viable role in the development process. The present status of libraries has to be seen in the light of the need for information in the various sectors of socioeconomic development and its actual achievements so far. The development of library system in India has not been even and balanced. Most of the well managed libraries and information centres are located in the major cities and, therefore, dissemination of information to the majority of the population living in the other areas of the country is not as per the felt need.
Department of Culture Ministry of Human Resource Development
Department of Culture Ministry of Human Resource Development